BCPT: Participant Update - K. Smigel (JNCI Journal of the National Cancer Institute, 1994)
Chlorpyrifos (CP) is an organophosphate insecticide that induces neurotoxicity through acetylcholinesterase (AChE) inhibition and redox imbalance, raising environmental and occupational health concerns. Plant-derived compounds from Senecio brasiliensis, native to the Pampa biome, offer multitarget therapeutic potential. This study evaluated the protective effects of the hydroalcoholic extract of S. brasiliensis (HESB) against CP-induced toxicity in Drosophila melanogaster (Harwich strain). Adult females (3-5 days old) were exposed for 48 h to control (1% sucrose), CP (0.25 ppm), HESB (1 mg/mL) or CP + HESB. CP increased mortality (37.3% ± 6.6%; p < 0.001) and impaired locomotion in the negative geotaxis (17.2 ± 3.0 s; p < 0.001) and footbridge (52.2 ± 5.2 s) assays, decreased AChE, GST and CAT activity (-31.8%, -45.8% and -72.3%, respectively; p = 0.006, 0.025 and 0.006), elevated ROS (+97.0%; p = 0.007), nitrite (+13.1%; p = 0.006) and TBARS (+25.6%; p = 0.010), depleted NPSH (-29.2%; p = 0.003) and PSH (-35.9%; p = 0.013) and reduced cell viability (-17.9%; p = 0.013). HESB co-treatment attenuated all CP-induced alterations, bringing parameters to control-comparable values (p > 0.05). These findings indicate that HESB exerts neuroprotective effects against CP toxicity through modulation of cholinergic function, attenuation of oxidative and nitrosative stress and preservation of thiol homeostasis.